Adaptive data gathering mechanism in opportunistic mobile sensor networks - SUN Li-min1; XIONG Yong-ping2; 3 (Tongxin xuebao)
An adaptive data gathering scheme was proposed for the application which different transmission quality was needed for different kinds of data. In the scheme, every sensor was associated with a forwarding probability parameter; every message was associated with an importance factor parameter. The two parameters determined adaptively the count of replication of a message, while meeting the transmission quality requirement and minimizing the network overhead. Experiment results show that the proposed data gathering scheme can achieve the tradeoff between transmission per- formance and network overhead.